Training of Socially Vulnerable Professionals in Solar Photovoltaic Microgeneration - Valentim, José Américo (Guará Journal, 2018)
The  solar  photovoltaic  generation  is  in  expansion due to  its  environment-friendly  facet,  decreasing costs, new  legislation,  national  fabrication of solar panels, and the rise in energy bills. In order to facilitate the deployment of the technology it is essential that there are both well-in-formed consumers and trained workforce. The Solar Photovoltaic Laboratory of UFJF holds accumulated experience in teaching, research, and demonstration activities related to the photovoltaic technology. Because of  the  demand  for  popularizing and  transferring  knowledge  in  science  and technology, this course was elaborated and promoted. Initially, this work reviews and remarks the importance of the solar photovoltaic mi-crogeneration and the main goals of the course. Subsequently, the main steps  of the preparation  and  execution  of  the  project  are described.  A  detailed  analysis  of  the  results  has revealed  that  the  target  group  has  been  reached and those  who  were  awarded  the  certificate  have  been adequately trained.
Keywords: Education in engineering; Renewable energy; Solar photovoltaic microgeneration; Technical training